The Ability to Memorize the Qur’an: How Does the Effectiveness of the Wahdah and Sima’i Methods? - Syifa Adilla Zahra; Nurul Azizah; Imam Syafe’i; Syaiful Anwar; Erni Yusnita (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2025)
The purpose of this study is to assess the effectiveness of the Wahdah and Sima’i methods in enhancing the ability to memorize the Qur'an, as well as to examine the differences in effectiveness between these two methods. This research employs a quantitative approach with a quasi-experimental design. The population in this study consists of eighth-grade students who use the Wahdah method, Sima’i method, and conventional methods. "The Wahdah method is a memorization technique where the verses to be memorized are learned one by one. The Wahdah method is a memorization approach in which the verses to be committed to memory are studied individually, one at a time. The sample for the study includes eighth-grade students who are willing to complete the distributed questionnaire. The sampling technique used in this study is a probability sampling technique with the type of simple random sampling, which involves randomly selecting samples from class H, where the researcher selects two classes consisting of an experimental class and a control class. The questionnaire is designed to uncover the success of a study, with statements based on a Likert scale consisting of five response options: Strongly Agree (SA), Agree (A), Neutral (N), Disagree (D), and Strongly Disagree (SD) to measure the attitudes, opinions, and perceptions of the participants. The instrument in this study includes statements based on the Likert scale according to the indicators proposed by Toyyib, which consist of three indicators: (1) The fluency of reading the memorized Qur'an, (2) The accuracy of applying the tajwid rules in reading the memorized Qur'an, (3) The fluency in reading the memorized Qur'an. There are 21 items in the questionnaire, which have been validated by a validator. The questionnaire was then pilot tested on a class outside the sample, after which the pilot test data was analyzed for validity. The number of valid statements identified was 14, and the questionnaire was subsequently distributed to respondents in the experimental and control classes. The data collected will undergo validity and reliability testing. Validity reflects how well the measurement instrument is able to measure what it is intended to measure and how relevant the instrument is to the measurement goals. Reliability is used to evaluate whether the data collection tool shows consistency, accuracy, stability, or reliability in revealing certain phenomena. Cronbach’s Alpha is used to evaluate the consistency of the results. Normality and homogeneity tests will then be conducted to determine if the data is normally distributed and to assess whether the data has similar characteristics. To assess the significance level, this study will perform a One-Way ANOVA test to determine the significant differences between the experimental and control groups. The analysis results show that both the Wahdah and Sima’i memorization methods have a positive impact on students' memorization abilities, although not all statistical analyses reveal significant differences. This study concludes that the application of innovative memorization methods can enhance the quality of memorization skills, particularly in the subjects of Quran and Hadith.